Dealing with ambush? Improving marketing strategies through NOC'S experience and consumer's perception - Pancic, Sanja Nadica (Πανεπιστήμιο Πελοποννήσου, 2014)
Olympic Games represent one of the biggest association sport events in the world that offers ideal platform for different promotional activities. Close with the Olympic Games symbolize very valuable and desirable motion for sponsors and partners. However, only limited numbers of corporation is in a position to acquire such reference due to the exclusivity offer and high cost of the sponsorship arrangements. This paper tends to explore the phenomenon and position of sponsorship and ambush marketing in Serbia, examining consumer`s perception and attitudes. Total sample of 203 was administered in various markets in two cities of interest (Belgrade and Knjazevac) complemented by the semi-constructed interview with the marketing manager of the National Olympic Committee (NOC). Results from this study contributed to the previous literature findings on ambush marketing, reaffirming ambush practices as unethical, unfair and inappropriate. These findings suggest that consumers are ready to show higher support for the official sponsors if able to distinguish them and if it is clear that profit help athletes. However low recognition and knowledge of sponsors among consumers indicates that sponsors should wisely and more intensively use the opportunities to associate with Olympics in order to establish deeper connection with the public. Overall, the results provide evidence that ambush marketing do not represent a serious problem in Serbia now, thus the biggest challenge for the NOC is to break through the clutter and increasing the consumers’ knowledge towards sponsorship. It is recommended that the NOC and sponsors should intensify joint activation and help sponsors to position themselves in the public and take all the advantages of being an Olympic partner. Future research on sponsors’ attitude and knowledge about Olympic imaginary could add to better understanding and usage of the sponsorship activation.
Keywords: Sports sponsorship - Serbia; Sports sponsorship - Law and legislation - Serbia; Sports - Marketing; Consumer behavior; Olympics; Αθλητισμός - Μάρκετινγκ - Σερβία; Αθλητική χορηγία - Δίκαιο και νομοθεσία - Σερβία; Αθλητισμός - Μάρκετινγκ; Συμπεριφορά καταναλωτών; Ολυμπιακοί αγώνες